2010
DOI: 10.1159/000314340
|View full text |Cite
|
Sign up to set email alerts
|

Does Washing the Biopsy Needle with Povidone-Iodine Have an Effect on Infection Rates after Transrectal Prostate Needle Biopsy?

Abstract: Purpose: To determine the effect of washing the biopsy needle with povidone-iodine solution on infection rates after transrectal ultrasonography-guided prostate biopsy. Patients and Methods: 180 patients with transrectal prostate biopsy were included. Infection was excluded with midstream urine culture before biopsy, and patients were divided into two groups. In group 1 (n = 84), the needle was washed with povidone-iodine after each material reception during biopsy, and in group 2 (n = 96), it was not. At day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 56 publications
0
16
1
Order By: Relevance
“…The results of the study reported that no difference was found between the povidone-iodine group and control group in terms of infective complications [28]. The results obtained in that study do not comply with our study results.…”
Section: Discussioncontrasting
confidence: 81%
“…The results of the study reported that no difference was found between the povidone-iodine group and control group in terms of infective complications [28]. The results obtained in that study do not comply with our study results.…”
Section: Discussioncontrasting
confidence: 81%
“…There are two older studies that are in agreement with our study (10, 13). A reverse result was reported by Koc et al (12). They enrolled 180 patients and used a needle that was washed with povidone-iodine for the povidone-iodine prescribed group.…”
Section: Discussionmentioning
confidence: 47%
“…Antibiotic premedication is used routinely to decrease this complication (2, 3, 4), but despite the use of antibiotics, infection develops in many patients with various degrees, from pyuria without clinical symptoms to life-threatening septicemia (5, 6, 7). Different additional methods have been studied for reducing the rate of infection following TRUS guided biopsy including the use of cleansing enema before the procedure (8, 9, 10, 11, 12, 13, 14, 15). However, the results are different.…”
Section: Introductionmentioning
confidence: 99%
“…Taylor et al showed that targeted antimicrobial prophylaxis based on rectal swab cultures may reduce the incidence of post-operative infectious complications and cost of care in patients undergoing TRUS-guided prostate biopsy [22]. In contrast, Koc et al reported that in a randomized controlled trial of 180 patients, washing of the biopsy needle with povidone-iodine solution did not reduce the rate of infection after transrectal needle biopsy of the prostate [23]. Bruyere et al, in a prospective cohort of 353 patients, reported that the routine bacterial culture of urine before prostate biopsy was not useful for antibiotic prophylaxis [24].…”
Section: Discussionmentioning
confidence: 99%